2021
DOI: 10.1186/s13071-021-04703-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical transmission of SARS-CoV-2 by house flies

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a recently emerged coronavirus that is the causative agent of the coronavirus disease 2019 (COVID-19) pandemic. COVID-19 in humans is characterized by a wide range of symptoms that range from asymptomatic to mild or severe illness including death. SARS-CoV-2 is highly contagious and is transmitted via the oral–nasal route through droplets and aerosols, or through contact with contaminated fomites. House flies are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 36 publications
(47 reference statements)
3
31
0
Order By: Relevance
“…SARS-CoV-2 was first detected in New Haven in March 2020, nine months after the current fly survey began. While the World Health Organization considers the flies' role in the transmission of the virus to again be incidental [129] research is starting to emerge demonstrating that flies are capable of transmitting SARS-CoV-2 and that infected flies are present in field samples from infected communities [130,131]. As the pandemic continues across the US and the world, an increase in fly surveys should be anticipated, providing the impetus to generate further comparative studies of domestic filth flies.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 was first detected in New Haven in March 2020, nine months after the current fly survey began. While the World Health Organization considers the flies' role in the transmission of the virus to again be incidental [129] research is starting to emerge demonstrating that flies are capable of transmitting SARS-CoV-2 and that infected flies are present in field samples from infected communities [130,131]. As the pandemic continues across the US and the world, an increase in fly surveys should be anticipated, providing the impetus to generate further comparative studies of domestic filth flies.…”
Section: Discussionmentioning
confidence: 99%
“…The flies need to acquire the virus from a contaminated surface and afterward harbor it on their gut or body surfaces to transmit it mechanically. The study results indicated that flies do not play a significant role in transmitting SARS-CoV-2 to humans and animals (Balaraman et al 2021a , b ).…”
Section: Transmission Of Sars-cov-2 By Insect Vectorsmentioning
confidence: 97%
“…It was tested whether mosquitoes are susceptible to SARS-CoV-2 by an oral route of infection, which was not previously evaluated. The study concluded that insects do not play an essential role in transmitting SARS-CoV-2 to humans (Balaraman et al 2021a , b ).…”
Section: Transmission Of Sars-cov-2 By Insect Vectorsmentioning
confidence: 99%
“…Recent studies demonstrated that SARS-CoV-2 replication was not supported in biting midges ( Culicoides sonorensis ) and mosquitoes ( Aedes aegypti, Aedes albopictus, Culex pipiens, Culex quinquefasciatus , and Culex tarsalis ), suggesting that these species are unable to be biological vectors of SARS-CoV-2 ( Balaraman et al, 2021a ; Fortuna et al, 2021 ; Huang et al, 2020c ). However, it has been demonstrated that houseflies ( Musca domestica ) can acquire and harbor infectious SARS-CoV-2 for up to 24 hours post-exposure ( Balaraman et al, 2021b ).…”
Section: Pests As Vehicles For Mechanical Transmission Of Sars-cov-2mentioning
confidence: 99%
“…It was reported that rodents and arthropods were involved in the mechanical transmission of the turkey coronavirus and SARS-CoV during the SARS epidemic ( Calibeo-Hayes et al, 2003 ; Reuben et al, 2020 ). Experimental studies showed that houseflies were able to mechanically transmit SARS-CoV-2 genomic RNA to the surrounding environment up to 24 h post-exposure ( Balaraman et al, 2021b ). Some of the United States’ common rodents, such as fox squirrels ( Sciurus niger ), Wyoming ground squirrels ( Urocitellus elegans ), house mice ( Mus musculus ), and black-tailed prairie dogs ( Cynomys ludovicianus ), are not susceptible to SARS-CoV-2 infection ( Bosco-Lauth et al, 2021 ).…”
Section: Pests As Vehicles For Mechanical Transmission Of Sars-cov-2mentioning
confidence: 99%